Implementasi Mentoring dalam Proses Pembelajaran CNC Pada Siswa Kelas XI Konsentrasi Keahlian Teknik Pemesinan di SMK - Hadyan Mawarid Mukti Prastama; Didik Nurhadi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study was motivated by the complexity of teaching Computer Numerical Control (CNC) in vocational high schools, which is often hindered by the disparity between limited practical facilities and the number of students. The objective of this study is to conduct an in-depth analysis of the implementation of mentoring in the CNC learning process among 11th-grade Machining Technology students at SMK PGRI 3 in Malang City. Using a descriptive qualitative approach, data were collected through in-depth interviews with four students as primary informants, two mentors as agents of innovation, and one practicing teacher as a validator, employing source triangulation. The results indicate that mentoring effectively reduces operational anxiety and enhances students’ self-efficacy in exploring complex geometric designs. This mentoring process facilitates the deep transfer of tacit knowledge, particularly regarding the accuracy of machine zero-point determination and an understanding of precision down to the micron level aspects not fully accommodated by digital simulation tools. In conclusion, the triadic synergy between students, mentors, and teachers creates a learning ecosystem that is accountable and aligned with manufacturing industry standards. This study recommends the development of a formal mentoring model integrated into the vocational curriculum to optimize the sustainable utilization of productive workshops.